Aplicación de una “auditoría tributaria en la distribuidora “disprac” (distribuidora de productos Álvarez Corrales) ubicada en la parroquia Eloy Alfaro del cantón Latacunga, provincia de Cotopaxi, al período del 1 de enero al 31 de diciembre del 2011 - Jácome Arequipa, Lorena Margoth (2017)
This searching work is for a tributary audit applied to the Distribuitor DISPRAC, in order to assess if the activities are proceeding according to planned objectives into the company and to detect the breach of tax obligations for determining the gaps efficient enforcement to prevent the declare dead time and play taxes in the “ SRI”. Among the techniques and methods used for analysis and data collection application of surveys, interviews and audit methodology by which positive and negative results within the entity were necessary. The tax audit was conducted to measure compliance with the obligations of the financial institution with the State using methods, techniques, auditing and tax laws that allow to compare and evaluate the process within the organization, to finally issue a final report contains conclusions and recommendations for the work done.